A message to Fukushima: nothing to fear but fear itself. (December 2016) - Sutou, Shizuyo
Abstract Introduction The linear no-threshold model (LNT) has been the basis for radiation protection policies worldwide for 60 years. LNT was fabricated without correct data. The lifespan study of Atomic bomb survivors (LSS) has provided fundamental data to support the NLT. In LSS, exposure doses were underestimated and cancer risk was overestimated; LSS data do not support LNT anymore. In light of these findings, radiation levels and cancer risk in Fukushima are reexamined. Results Soon after the Fukushima accident, the International Commission on Radiological Protection issued an emergency recommendation that national authorities set reference highest levels in the band of 20–100 mSv and, when the radiation source is under control, reference levels are in the band of 1–20 mSv/y. The Japanese government set the limit dose as low as 1 mSv for the public and stirred up radiophobia, which continues to cause tremendous human, social, and economic losses. Estimated doses in three areas of Fukushima were 0.6–2.3 mSv/y in Tamura City, 1.1–5.5 mSv/y in Kawauchi Village, and 3.8–17 mSv/y in Iitate Village. Since even after acute irradiation, no significant differences are found below 200 mSv for leukemia and below 100 mSv for solid cancers. These data indicate that cancer risk is negligible in Fukushima. Moreover, beneficial effects (lessened cancer incidence) were observed at 400–600 mSv in LSS. Living organisms, which have established efficient defense mechanisms against radiation through 3.8 billion years of evolutionary history, can tolerate 1000 mSv/y if radiation dose rates are low. In fact, people have lived for generations without adverse health effects in high background radiation areas such as Kelara (35 mSv/y), India, and Ramsar (260 mSv/y), Iran. Low dose radiation itself is harmless, but fear of radiation is vitally harmful. Conclusions When people return to the evacuation zones in Fukushima now and in the future, they will be exposed to such low radiation doses as to cause no physical effects. The most threatening public health issue is the adverse effect on mental health caused by undue fear of radiation.